Combined GPR and Self-Potential Techniques for Monitoring Steel Rebar Corrosion in Reinforced Concrete Structures: A Laboratory Study - Giacomo Fornasari; Luigi Capozzoli; Enzo Rizzo (Remote Sensing, 2023)
Steel rebar corrosion is one of the main causes of the deterioration of engineering reinforced structures. Steel rebar in concrete is normally in a non-corroding, passive condition, but these conditions are not always achieved in practice, due to which corrosion of rebars takes place. This degradation has physical consequences, such as decreased ultimate strength and serviceability of engineering concrete structures. This work describes a laboratory test where GPR and SP geophysical techniques were used to detect and monitor the corrosion phenomena. The laboratory tests have been performed with several reinforced concrete samples. The concrete samples were partially submerged in water with a 5% sodium chloride (NaCl) solution. Therefore, an accelerated corrosion phenomenon has been produced by a direct current (DC) power supply along the rebar. The geophysical measurements were performed with a 2.0 GHz centre frequency GPR antenna along several parallel lines on the samples, always being the radar line perpendicular to the rebar axis. The GPR A-scan amplitude signals were elaborated with the Hilbert Transform approach, observing the envelope variations due to the progress of the steel rebar corrosion in each concrete sample. Moreover, Self-Potential acquisitions were carried out on the surface of the concrete sample at the beginning and end of the experiments. Each technique provided specific information, but a data integration method used in the operating system will further improve the overall quality of diagnosis. The collected data were used for an integrated detection approach useful to observe the corrosion evolution along the reinforcement bar. These first laboratory results highlight how the GPR should give a quantitative contribution to the deterioration of reinforced concrete structure.